Stress Martensite Nucleation in a State of Premartensitic Lattice Instability - Y. V. Dolgachev; V. N. Pustovoit; Y. M. Vernigorov (Advanced Engineering Research, 2024)
Introduction. The combined effect on the phase transformation process, involving a combination of heat treatment and external action, is a major technology solution for obtaining the required properties of steel products. When hardening steel in a constant magnetic field with a strength of 1–2 MA/m, martensite formation is observed at higher temperatures. In addition, when compared to conventional hardening, there are changes in structure and properties. Such effects cannot be explained only in terms of thermodynamics, since the expected shift in the equilibrium temperature between austenite and martensite in a magnetic field of such strength does not exceed 4–8°C. To explain the effects that occur during hardening in a magnetic field, it is proposed to consider the features of martensitic transformation in highspeed steel when exposed to an external magnetic field in the temperature range of austenite superplasticity. This research was aimed at identifying the features of martensitic transformation in the presence of a constant magnetic field in steel with account for the phenomena occurring in the premartensitic state.Materials and Methods. Samples made of steel R6M5 were used. Characteristics of the martensitic transformation were studied using the potentiometric method of electrical resistance. The data were recorded using an L-CARD E14-440 analog-to-digital converter with the LGraph2 software package. The sample was heated by passing current. The sample was placed in the interpolar space of an open-type laboratory electromagnet FL-1, which provided the creation of a magnetic field with a strength of 1.2 MA/m.Results. The obtained differentiated dependences were characterized by electrical resistance anomalies (low-temperature peaks) at a temperature corresponding to the appearance of a ferromagnetic phase as a result of martensitic transformation. In a magnetic field, the development of martensitic transformation began at a higher temperature, which could not be explained in terms of thermodynamics. Thus, the formation of stress martensite was observed in microvolumes of austenite with ferromagnetic ordering, which perceived the energy of the external field through magnetostrictive stresses. Under conditions of superplastic austenite, such stresses were sufficient to initiate shear transformation. The minimum possible size of lattice instability fluctuations (1.372 nm) was determined.Discussion and Conclusion. Exposure to a magnetic field under hardening intensified the processes of some magnetic decomposition of austenite. At temperatures close to the beginning of the martensitic transformation, the existing areas of magnetic inhomogeneity were superimposed on the effects of the phenomenon of instability of the crystal lattice. In the temperature range Md-Mn, when austenite exhibited superplasticity, the formation of stress martensite in microvolumes of austenite with ferromagnetic ordering was significantly facilitated